Retinoid Regulation of Antiviral Innate Immunity in Hepatocytes - Cho, Noell E. (Hepatology, 2016)
Persistent infection of HCV is one of the leading cause of end stage liver diseases such as decompensated cirrhosis and liver cancer. Of particular note, nearly half of HCV infected people in the United States are reported to be heavy drinkers. This particular group of patients are known to rapidly progress to the end stage liver diseases. Although, the accelerated disease progression among alcohol abusers infected with HCV is clinically well recognized, the molecular pathophysiology behind this manifestation has not been well elucidated. Hepatocytes metabolize ethanol (EtOH) primarily through two steps of oxidative catabolism in which alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) play central roles. The ADH-ALDH pathway also governs the metabolism of Retinol (Vitamin A) to its transcriptionally active metabolite, Retinoic Acid (RA). In this study, we defined that the ADH-ALDH pathway serves as a potent antiviral host factor in hepatocytes, which regulates the expression of Interferon Stimulated Genes (ISGs) via biogenesis of RA. ISGs constitute over 300 antiviral effectors, which cooperatively govern intracellular antiviral innate immunity. Our study revealed that intracellular RA levels greatly influence ISGs expression under basal conditions. Moreover, RA augments ISGs induction in response to viral infection or exposure to IFN in a gene-specific manner. Lastly, our results demonstrated that EtOH attenuates the antiviral function of the ADH-ALDH pathway which suggests the possibility that EtOH-Retinol metabolic competition is one of the molecular mechanisms for the synergism between HCV and alcohol abuse in liver disease progression. In conclusion, our study provides novel insights into the critical role of RA in the regulation of intracellular antiviral innate immunity in hepatocytes.